Digitalisasi Al-Qur’an :Transformasi dan Sakralitas Al-Qur’an - Rahma, Binti Khabibatur Rohmah Al Arifah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The transformation of the Qur'an in the digital era has brought significant changes to the way Muslims access, learn and practice the teachings in the holy book. In the development of information technology, especially digital-based applications, it has provided convenience in understanding the Qur'an through various platforms. The purpose of the research is to analyze the transformation of the Qur'an in the digital era by describing some of the main applications that are popular among people today, namely researchers taking two examples of digital Qur'an, Muslim Pro and Al Qur'an Apps (Tafsir & Perkata). In addition, it also analyzes the sacredness of the Qur'an. With digitalization, where the Qur'an will shrink when integrated in virtual or digital form, especially in the interaction of Muslims with the Qur'an. This research uses the library research method. To get a deeper understanding of the transformation as an impact on the sacredness of the Qur'an. The transformation that occurs has implications and challenges for Muslims to maintain their religious values, especially in the sacredness of the Qur'an.